The Aromanian-Romanian national movement (1859-1905): an analytical model - Creţulescu, Vladimir (Balcanica Posnaniensia. Acta et studia, 2015)
At the turn of the 20th century, Macedonia was a region still controlled by the waning Ottoman Empire, though intensely coveted by the neighbouring Balkan states, which deployed national propaganda movements in Macedonia, in preparation for future territorial annexations. It is this author’s contention that the “Macedonian question” thus engendered gives rise to several overlapping triadic configurations of interlocking, interacting and mutually monitoring nationalisms, as per the analytical model put forth by Rogers Brubaker. Working on this premise, and after adjusting Brubaker’s model to account for the specific relational settings of the Macedonian question, this author proceeds to draft a case study of a specific triadic configuration, among several operating in <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">fin-de-siècle Macedonia: namely, the one arisen out of the mutual monitoring and interaction of a Romanian nationalizing nationalism, a Greek nationalizing nationalism, and two Aromanian (or Vlach) minority nationalisms.